FISH COMMUNITY STRUCTURE IN RELATION TO WATER QUALITY OF THE DOWN STREAM OF MUSI RIVER, SOUTH SUMATERA, INDONESIA - Husnah Husnah; Eko Prianto; Makri Makri; Hilda Z. Dahlan (Indonesian Fisheries Research Journal, 2008)
Musi River is a large riverwith its drainage area covers three provinces, South Sumatera, Lampung, and Bengkulu, and with multi uses of its resources.